Investigating the Role of Optimism and Resilience on the Effect of Work Engagement on Emotional Exhaustion and Workplace Deviant Behaviors - Chiyangwa, Rumbidzai; Muponya, Isaac (International Journal of Scientific Research and Management (IJSRM), 2024)
Under what situations can work engagement predict emotional exhaustion? Working with the idea that work engagement and emotional exhaustion are two endpoints of a continuum, we relied on the conservation of resources (COR) theory – which evaluates them as two different variables – to undertake a multi-context, two-study research among bankers and miners. We asserted that work engagement would increase emotional exhaustion for people who are scaled lower in the optimism individual trait. Additionally, we recognized a three-way interaction, wherein work engagement heightened emotional exhaustion for less-optimistic persons who are also not resilient, while oppositely minimizing emotional exhaustion for high-optimism persons who are resilient. Our findings also lend credence to a moderated-mediation model, suggesting that when both optimism and resilience are high, deviant conduct in the workplace is reduced because workers are less emotionally exhausted from their work. We provide suggestions for future studies on work engagement and workplace deviant behavior.